Foreword: the inheritance of loss - Fisher, N (Refugee Studies Centre, University of Oxford, 2014)
As the civil war in Syria drags on, the scale of displacement continues to increase. While the crisis may be prolonged, refugees and IDPs need support now for their protection, their recovery, and both their immediate and their long-term prospects.